STATUS THERMAL COMFORT PADA LINGKUNGAN ATMOSFER PERMUKIMAN DI WILAYAH KECAMATAN DENPASAR BARAT - Edy Indrawan Kusuma, Komang; Kasa, I Wayan; Dhana, I Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 1 (2016)DO - 10.24843/EJES.2016.v10.i01.p02, 2016)
The effect of residential atmosphere environment generally gives environment stress to the life of the dwellers. One of the environment stress source is the unfulfilment of thermal comfort. The rapid development of residential at Denpasar City cause the variation on building density that are low, medium, high, and very high density classifications. Residential configuration of each classification gives very strong influence to status of urban’s thermal comfort. Purpose of the research is to understand the thermal index profile PET, to identify the status of thermal comfort and to analyze the influence of Tmrt to thermal index PET of residential atmosphere environment at West Denpasar Sub-district area. The research was performed at residential atmosphere environment of West Denpasar Sub-district area by using RayMan model simulation to obtain thermal index profile PET. Sampling technique used the stratified random sampling method with data diversity that is used based on the buildings density. The thermal index profile PET of residential of low density classification is the lowest thermal index profile PET compared to the other three classifications, which are the medium, high, and very high density. One hundred percent of status of thermal comfort of residential atmosphere environment is in hot thermal stress and based on average thermal index PET is on physiological stress level of “Strong heat stress”. Tmrt is the most influential variable to thermal index PET. The concept to increase the status of thermal comfort of residential atmosphere environment at West Denpasar area used the bioclimatic approach. Investigation of status of thermal comfort of residential atmosphere environment at West Denpasar Sub-district area has given the directive of urban planning in improving and revitalized urban spaces.
Keywords: Thermal Comfort, Thermal Index PET, Urban Bioclimatic, Atmosphere Environment